Perceptions of swine euthanasia among Brazilian caretakers from non-integrated swine farms - Alves, Laya Kannan Silva; Pairis-Garcia, Monique Danielle; Arruda, Andréia Gonçalves; de Melo, Cecília Archangelo Ferreira; Gomes, Nadia de Almeida Ciriaco; Hoshino, Roberta Yukari; Garbossa, Cesar Augusto Pospissil (Frontiers in Veterinary Science, 2025)
Timely and humane euthanasia is crucial for animal welfare on swine farms, yet challenges persist in its implementation, particularly in Brazil, where the responsibility often falls to caretakers lacking training. This study aimed to assess the knowledge, attitudes, and practices of swine caretakers regarding euthanasia across non-integrated farms (ranging from 1,000 to 3,500 housed sows) and different experience levels (from less than a month to 40 years working with pigs). A total of 117 people directly working with pigs participated in a survey designed to evaluate their decision-making skills, euthanasia competencies, and understanding of Brazilian guidelines for euthanasia methods. Using Cluster analysis, we identified two distinct groups of caretakers: (1) Empathetic, self-sufficient, apathetic about euthanasia; and (2) Empathetic, knowledge seeker, uncomfortable with euthanasia. Both Clusters exhibited high empathy toward pigs and confidence in identifying sick animals but differed in their attitudes toward euthanasia. The risk factor analysis showed a tendency for younger respondents (under 36 years old) and those from smaller farms (less than 2,000 sows) were more likely to belong to Cluster 2, while older caretakers (over 36 years) and those working on larger farms (more than 2,000 housed sows) tended to belong to Cluster 1. Furthermore, a significant proportion of caretakers lacked knowledge of the euthanasia Brazilian guidelines, as evidenced by incorrect responses regarding acceptable euthanasia methods, such as performing cardiac perforation or using non-penetrating captive bolt guns on growing-finishing pigs. This study highlights the variability in caretaker experience and attitudes toward euthanasia, suggesting a critical need for targeted training programs and euthanasia protocols that address both emotional and practical aspects. Improved understanding of caretaker attitudes can enhance both human and animal welfare on farms.